Use of unlocked intramedullary nailing in winquist type I and II femoral isthmus fracture - Ling, H.T.; Ng, W.M.; Kwan, M.K.; Aizuddeen, L.K.F.; Tay, P.C.M. (2008)
Interlocked intramedullary nailing is accepted as the gold standard for femoral shaft fractures. However for Winquist type I and II femoral fractures at the isthmus region, unlocked intramedullary nailing (Küntscher nailing) is still a good option. We performed a retrospective study on 86 patients with a total of 88 femoral shaft fractures around the isthmus that presented at our institution between 1 January 1988 and 31 August 2003. All patients (84.1 Winquist type I and 15.9 Winquist Type II fractures) were treated with unlocked intramedullary nail. The average time to union was 16 weeks with 97.7 rate of union. There were two cases (2.3) of infection and non-union each. Overall results were comparable to standard interlocking intramedullary nailing. We conclude that unlocked intramedullary nailing is a good treatment option for Winquist Type I and II femoral fracture around the isthmus with its good union rate and minimal complications.